From Richardson to Howells - Vail, Alice (My University, 1892)
Introduction: From the days of longsleeved aprons we have loved our storybooks. There it was the one with large, colored pictures that pleased us most. We wanted the Three Bears pictured vividly with immense teeth and shaggy coats; we wanted to see Red Riding Hood walking along engaged in a confidential conversation with a very large wolf. Now we do not care so much for the pictures. We have grown enough so that we want a good, well written story, and will accept nothing else, though the illustrations may be the finest which can be designed for a critical public. While we have more demand for good fiction than ever before, it is certainly true that we have every means by which to supply it. The poet inspired by the Muses, sings his songs of life and love and home; we have bequeathed to us the romance told by the man of old, giving to us astonishing information regarding the days of knights, fair ladies and wild beasts; but better than all, in the novel, that seek growth of the years, we have our most profitable and most entertaining form of fiction.
Citation: Vail, Alice. From Richardson to Howells. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Fiction; English; Richardson; Novel; Literature; Theses; Manuscripts (documents)